2002
DOI: 10.1017/s0950268802007483
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of Staphylococcus aureus control in dairy herds

Abstract: An ordinary differential equation model was developed to simulate dynamics of Staphylococcus aureus mastitis. Data to estimate model parameters were obtained from an 18-month observational study in three commercial dairy herds. A deterministic simulation model was constructed to estimate values of the basic (R0) and effective (Rt) reproductive number in each herd, and to examine the effect of management on mastitis control. In all herds R0 was below the threshold value 1, indicating control of contagious trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(126 citation statements)
references
References 40 publications
2
115
0
9
Order By: Relevance
“…Antibiotics on dairy operations are used to treat highly prevalent infections, such as subclinical mastitis, and as a preventive measure during dry cow therapy (Zadoks et al, 2002). Monitoring the emergence of resistant pathogens in animal reservoirs is important particularly for those with zoonotic potential (Normanno et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics on dairy operations are used to treat highly prevalent infections, such as subclinical mastitis, and as a preventive measure during dry cow therapy (Zadoks et al, 2002). Monitoring the emergence of resistant pathogens in animal reservoirs is important particularly for those with zoonotic potential (Normanno et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown an impact of mastitis control programs in reduction of the prevalence and incidence of mastitis (Barkema et al 1998b;Neave et al 1969;Hillerton et al 1993;Hillerton et al 1995;Zadoks et al 2002). Success is particularly easy to achieve in the case of S. agalactiae mastitis (Loeffler et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Control of S. aureus mastitis is often deemed to be difficult, but many herds have been successful in this regard through implementation of the standard mastitis prevention program (e.g. Hillerton et al 1995;Zadoks et al 2002). The standard mastitis prevention program also affects the prevalence and incidence of S. dysgalactiae and S. uberis (Neave et al 1969), regardless of the often used and misleading label of 'environmental streptococci'.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations